Prospects for Applying the Integrated Approach «Fire Safety + Engineering + Work-at-Height Technologies» for Sustainable Infrastructure Development - Valentyn Ishchenko (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Against the backdrop of rapid global urbanization and the expansion of high-rise construction, the architecture, engineering, and construction sector faces a dual imperative: to guarantee an unprecedented level of fire safety while simultaneously achieving sustainability targets. Prevailing practices in the design, construction, and operation of high-rise assets remain largely fragmented: safety subsystems, engineering solutions, and digital technologies are developed and deployed in isolation, which erodes synergistic effects and hinders the formation of a truly resilient and sustainable urban infrastructure. In response to this challenge, a holistic tripartite conceptual framework is proposed that integrates principles of fire safety, advanced engineering solutions, and high technologies. The research methodology includes a systematic literature review to inventory existing technologies and identify research gaps, as well as a qualitative comparative analysis of representative cases. The article details the key technological components of the proposed framework — Building Information Modeling (BIM), the Internet of Things (IoT), artificial intelligence (AI), and digital twins (DT). Their role is demonstrated in shaping an integrated, intelligent, and adaptive building ecosystem. The analysis identifies significant technical, organizational, economic, and educational barriers to implementing such a comprehensive approach. In conclusion, it is substantiated that the proposed integrated foundation is critically important for achieving the United Nations Sustainable Development Goals, primarily SDG 9 and SDG 11, and practice-oriented recommendations are formulated for the professional community, policymakers, and academia to accelerate the transition to a new generation of sustainable and safe vertical cities.